ESTIMATION OF EMISSION TAX VALUE OF HOSPITALITY AND RESTAURANT INDUSTRY IN BOGOR CITY, WEST JAVA, INDONESIA - Go, Riska Tezara; Aini, Nur; Renjaan, Irene Paula (Institut Teknologi Nasional, Bandung, 2024)
The number of hotels and restaurants in Bogor City has increased annually. According to the Bogor City Tourism and Culture Office (2018), the number of hotels rose from 53 units in 2016 to 87 units, while restaurants increased from 162 units to 680 units. This growth leads to higher CO2 emissions, while green open spaces remain static. This study aims to estimate CO2 emissions from the hotel and restaurant industry using the TIER-1 method, determine the urban park land needed to absorb these emissions using a quantitative descriptive approach, estimate the CO2 emission tax value based on the cost of creating urban parks, and propose alternative policy implications for emission tax implementation using a qualitative descriptive approach. The results indicate that hotels in Bogor City produce 3221 tons of CO2 per year, and restaurants produce 9583 tons per year. The current green open spaces are insufficient to absorb these emissions, necessitating additional urban park land. Specifically, the hotel industry requires 57 hectares of city park, and the restaurant industry requires 167 hectares. Funding for the development of these parks is to be sourced from emission taxes levied on hotels and restaurants. The proposed emission tax is Rp 3415 per room per night for hotels and Rp 239 per transaction for restaurants.